La desnutrición y su incidencia en el desarrollo psicomotriz de las niñas y niños del primer año de educación básica del jardín de infantes “Ciudad de Quinindé” del cantón Quinindé de la provincia de Esmeraldas del período lectivo 2013–2014 - Naranjo Alvarez, Lorena del Rosario (2014)
This research work entitled "MALNUTRITION AND ITS IMPACT ON BASIC EDUCATION FIRST YEAR CHILDREN PSYCHOMOTOR DEVELOPMENT “CIUDAD DE QUI NINDÉ KINDERGARTEN" ESMERALDA PROVICE ACADEMIC YEAR 2013 – 2014. It has been structured and developed in accordance with the regulations in force graduation from the National University of Loja. In the present investigation was the General Objective: To investigate whether malnutrition affects the psychomotor development of children from the First Year of Basic Education. The methods used in the preparation of this research work were: Scientist, Deductive and Inductive Statistical Model, which allowed for the discussion and comparison of the proposed variables. Two instruments were applied. Survey parents of first year Basic Education Kindergarten "Quinindé City" to identify the causes of malnutrition and Denver Test girls and children in the first year of Basic Education of the Kindergarten "City Quinindé" to observe the degree of motor skills. The results of the survey it was determined that 49.4% of mothers said they did not have a good diet during pregnancy and only 53.1% gave him exclusive breastfeeding for the child during the first 6 months, plus that 67.9% of mothers said they provide five meals during the day, this being the number recommended for children meals with optimal development, another key point to emphasize is that only 23.5% of mothers said their children provide a balanced diet containing foods from the 4 food groups like carbohydrates protein fruits and vegetables. According to the test the results were of 81.64% of children had a good thick psychomotor development while 18.36 presented several shortcomings in this area, and with respect to the 85.49 fine motor skills of children successfully responded activities while 14, 51 did not achieve its goal malnutrition in early life causes a deficit of growth, psychomotor development and learning ability of the child